Training Workshop on Teaching/Learning in Health Professions Education for Medical Teachers: Feedback of the Participants - Piryani, Rano Mal; Ali Afsar, Nasir; Zebe, Nudrat; Piryani, Suneel (Medical Journal of Eastern Nepal, 2024)
Background: For enhancing teaching skills of faculty members, 3-day Training Workshop on Teaching/Learning in Health Profession Education was organized at Bilwal Medical College Liaquat University of Medical and Health Sciences Jamshoro Sindh Pakistan.  Main objective of the study was to assess feedback of the participants at New World Kirkpatrick’s Model level 1 and 2.Methods: This was cross-sectional study conducted using self-administered questionnaire. The questionnaire had 5-parts; 1) Demographics; 2) Rating of participants on attributes of training workshop at scale 1-10 (1=poor, 10=excellent); 3) Confidence level of the participants on skills learned in specific session at Likert scale 1-4 (1=Not-confident, 4=Extremely-Confident) on retro-pre-questionnaire; 4) Open-ended questions on strengths of workshop and 5) areas for improvement. The data was analyzed for central tendency. The data of retro-pre-questionnaire was normally distributed, so, t-test used for comparison of means. Data of open-ended questions was sorted manually.Results: The rating on attributes of training workshop i.e. usefulness (8.59±1.18), content (8.53±1.12), relevance (8.59±1.23) and facilitation (9.18±0.95) was notable and overall (8.82±0.95) too. The perceived confidence level of participants was significantly (< 0.001) enhanced on five Skills Learned in Specific Sessions of Training Workshop: developing learning objectives (before 2.24±0.44, after 3.29±0.47 ); developing effective PowerPoint presentation (before 2.59±0.51, after 3.06±0.56), conducting large group teaching (before 2.53±0.72, after 3.12±0.60), developing lesson plan for teaching (before 2.12±0.60, after 3.18±0.64), and conducting small group teaching (before 2.76±0.75, after 3.41±0.51)Conclusion: Overall reaction of the participants was constructive and their confidence level was significantly enhanced on specific skills related to teaching/learning.